2004
DOI: 10.1038/ncb1107
|View full text |Cite
|
Sign up to set email alerts
|

GGA proteins bind ubiquitin to facilitate sorting at the trans-Golgi network

Abstract: Ubiquitination functions as a sorting signal for lysosomal degradation of cell-surface proteins by facilitating their internalization from the plasma membrane and incorporation into lumenal vesicles of multivesicular bodies (MVBs). Ubiquitin may also mediate sorting of proteins from the trans-Golgi network (TGN) to the endosome, thereby preventing their appearance on the cell surface and hastening their degradation in the lysosome-vacuole. Substantiation of a direct ubiquitin-dependent TGN sorting pathway reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
165
1
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(180 citation statements)
references
References 28 publications
7
165
1
7
Order By: Relevance
“…The known functions of ARF proteins and the ARD1 ARF domain might indicate an association with Golgi structure and lysosomes in processes related to vesicular transport. Relationships among ubiquitin, trans-Golgi network, and endosomal compartments have been reported (48,49). These studies demonstrated that Golgi-localized, gamma-ear-containing, ARFbinding (GGA) proteins bind ubiquitin through their GAT domains to accomplish protein sorting at the trans-Golgi network and transport toward endosomes.…”
Section: Discussionmentioning
confidence: 97%
“…The known functions of ARF proteins and the ARD1 ARF domain might indicate an association with Golgi structure and lysosomes in processes related to vesicular transport. Relationships among ubiquitin, trans-Golgi network, and endosomal compartments have been reported (48,49). These studies demonstrated that Golgi-localized, gamma-ear-containing, ARFbinding (GGA) proteins bind ubiquitin through their GAT domains to accomplish protein sorting at the trans-Golgi network and transport toward endosomes.…”
Section: Discussionmentioning
confidence: 97%
“…Mutation of leucine 280 in site 2 of the human Gga3 GAT domain results in a complete loss of interaction with mono-ubiquitin-agarose (28) or GST-ubiquitin (22), although a GST-Gga3-GAT fusion protein with this mutation demonstrated reduced but detectable binding to mono-and polyubiquitin by pulldown and surface plasmon resonance (23). Yeast Gga1 and Gga2 also have been shown to bind ubiquitin (22,27), but the ubiquitin-binding sites have not been mapped in the yeast Gga proteins. We introduced a mutation in the GAT domain of yeast Gga2 (L303A) that corresponds to the Leu-280 site 2 mutation of human Gga3 (Fig.…”
Section: Loss Of Ubiquitin Binding With Mutation Of a Site 2 Leucinementioning
confidence: 99%
“…The amino-terminal VHS domain of mammalian Ggas binds to an acidic di-leucine sorting signal defined by the consensus motif DXXLL, which is located in the cytosolic domain of cargo proteins; however, in yeast, cargo proteins do not contain this type of motif, and the residues of the VHS domain of human Ggas that bind this motif are not conserved (20,21). The GAT domain of human Gga3 also contains two binding sites for ubiquitin, and a number of conserved hydrophobic amino acid residues in the carboxylterminal half of the GAT domain have been shown to directly contribute to ubiquitin binding at the two sites (22)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%
“…Experimental evidence is needed to determine whether the modified UIM motif of the Arabidopsis and rice VHS domain proteins is functional (see Supplementary material Table S1). Ubiquitin binding and delivery of cargo proteins to the putative plant ESCRT-machinery might also be mediated by proteins with a GAT (GGA and TOM1) domain, which has been shown to bind ubiquitin in a similar mode as the UIM and is necessary for the transport of monoubiquitinated cargo proteins to the MVB pathway [34][35][36]. The proximity of a VHS domain is necessary for efficient binding of ubiquitin to GAT domains.…”
mentioning
confidence: 99%